Strategic Studies and the New Geopolitical International Scenario - Metushaj, Mirela; Luli, Elira (Acta Universitatis Danubius. Relationes Internationales, 2024)
This paper explores the evolving field of strategic studies in light of the new geopolitical international scenario characterized by multipolarity, hybrid warfare, and technological competition. It examines the historical development of strategic studies, the implications of contemporary geopolitical trends, and the need for adaptation within the field to address complex security challenges. Ultimately, it argues that a redefined approach to strategic studies is essential for effective policy formulation and national security in an increasingly interconnected and contested world. Strategic studies is an interdisciplinary field that focuses on the analysis of power dynamics, military strategy, and national security within the broader framework of international relations. It encompasses the examination of how states and non-state actors utilize power to achieve their objectives, particularly in the realm of conflict and security.